Potensi Bakteri Asam Laktat (BAL) Dari Jus Tempe Sebagai Kandidat Probiotik - Aýun, Qurrota; Muthiáh, Sari Niswatul; Sukmalara, Dini (Universitas Al Azhar Indonesia, 2023)
Tempeh is a substrate that can be metabolized by Lactic Acid Bacteria (BAL) so that it can be used to maintain the balance of intestinal microflora. BAL belongs to non-pathogenic bacteria that produce lactic acid as the main end product. The probiotic property of BAL contained in tempeh juice with the addition of dates and skim milk need to be tested biochemically. This study aims to measure the BAL potential of tempeh juice as probiotic candidate. The total BAL measurement is carried out by counting the Total Plate Count (TPC). The method is carried out using macroscopic, microscopic and biochemical characteristics (catalase test, salt content resistance test, and acid pH resistance test). The data is descriptively presented using figures and tables. This method obtained a total BAL of 9.6 x 106 cfu/ml, which meets the requirement for growing probiotics of at least 106 cfu/ml. Macroscopic characterization shows colonies in the form of rounds, flat edges, convex elevations, and around the colony there was a clear zone. Microscopic characterization obtained four isolates that are Gram-positive, catalase negative, resistant to salt content of 5% and 6.5% and able to grow at pH 2.5 and 3. Based on this study, four isolates were found to have the potential to be probiotic candidates.Keywords – Dates, Lactid Acid Bacteria, Skim Milk, Tempeh, Probiotic